(untitled) (Mustansiria Dental Journal, 2019)
Background:Geographic tongue or erythema migrans is fairly common benign condition that primarily affects the lateral aspect and dorsum of the tongue. The pattern of the lesion give the surface of the tongue the appearance of a map, the lesion persists for a short period in one area, disappears within a few days, and then recurs in another area with no apparent reason Although the etiology of the condition is unknown, it may be related to psychological factors. The aim of this study is to evaluate the association between geographic tongue and stress. Method:This study was performed on 110 individuals; 60 cases with GT and 50 cases without GT. All of them filled a questionnaire of perceived stress scale (PSS) and evaluated by a psychologist. Results:Among 120 patients selected, 60 persons suffered from geographic tongue, showed significant relationship between the occurrence of geographic tongue and stress especially among females at their third decade. Conclusion:According to the results, there is a significant association between stress and GT and decreasing stress in GT patients can lead to the healing of the lesion.